Dispositif De Formation Et D’évaluation Du Stage De Fin De Cycle : Premiers Constats - Somaya El Gharras; Jamila Charki (European Scientific Journal, ESJ, 2016)
The evolution of society brings new requirements for the citizen of tomorrow and consequently to the future's school. It is the duty of every society to worry about the support provided for the citizen's construction. The school being a key in the development of the individual, the main actors of this system must be properly supported in their training. The reform concerning training of teachers in Morocco is a part of the professionalization process through the creation of Regional Centers of Educational Professions and Training (CRMEF) who have a qualifying mission. These centers complement the training begun in the university education tracks (FUE). Previous training of Moroccan teacher who was held in the teacher training schools (ENS) included a significant practical training. However, capitalization of experiences from one year to another was insufficient. Leaving few traces the efforts made were not shown at fair value. In this work, we stopped on training, coaching and evaluation methods used on the Master specialized on educational professions provided in teacher training school (ENS) which is an institution in Cadi Ayyad University at Marrakesh. In this context, we propose a system which takes into account the different components of the activity of training. We assume that one of the advantages of this device is the reflexive dimension brought by the competence approach both for the teacher and the student. A second interest lies in the method adopted to evaluate the productions of trainees, like a competency referential to validate through a distance learning platform.